Operational Efficiency and Risk Management: Implications for the Financial Performance of the Jakarta Regional Development Bank - Bambang Jatmiko (International Publisher (YAPENBI), 2025)
This study aims to analyse the factors that affect the Return on Equity (ROE) at the Jakarta Regional Development Bank (BPD) during the period 2017Q1–2024Q4. Using a multiple regression approach, the variables tested included BOPO (Operating Costs to Operating Income), NPLs (Non-Performing Loans), LDR (Loan to Deposit Ratio), and Reserve Requirements (Minimum Required Current Accounts). The regression results showed that BOPO and NPL had a significant negative influence on ROE, while LDR and reserve requirement had a significant positive influence. This regression model has an R-squared of 0.9570, which indicates that almost 96% of the variation in ROE can be explained by the variables studied. This research confirms that operational efficiency and credit risk management are very important in increasing bank profitability. Therefore, it is recommended that BPD DKI Jakarta focus on reducing operational costs, strengthening credit risk management, and managing balanced liquidity to maximize ROE. These findings provide practical insights for strategic policy making in improving the financial performance of regional development banks in Indonesia.